Metallic coating thickness assessment over nonmagnetic metals using eddy current technology - Ansari, Zain Ali (2019)
A Master of Science thesis in Mechanical Engineering by Zain Ali Ansari entitled, “Metallic coating thickness assessment over nonmagnetic metals using eddy current technology”, submitted in April 2019. Thesis advisor is Dr. Bassam Abu-Nabah and thesis co-advisor Dr. Maen Alkhader. Soft and hard copy available.